Placing movies : the practice of film criticism - Rosenbaum, Jonathan, 1943- (Berkeley : University of California Press, 1995)
Jonathan Rosenbaum, longtime contributor to such publications as Film Quarterly, Sight and Sound, and The Village Voice, is arguably the most eloquent, insightful film critic writing in America today. Placing Movies, the first collection of his work, gathers together thirty of his most distinctive and illuminating pieces. Written over a span of twenty-one years, these essays cover an extraordinarily broad range of films--from Hollywood blockbusters to foreign art movies to experimental cinema. They include not just reviews but perceptive commentary on directors, actors, and trends and thoughtful analysis of the practice of film criticism. It is this last element--Rosenbaum's reflections on the art of film criticism--that sets this collection apart from other volumes of film writing. Both in the essays themselves and in the section introductions, Rosenbaum provides a rare insider's view of his profession: the backstage politics, the formulation of critical judgments, the function of film commentary. Taken together, these pieces serve as a guided tour of the profession of film criticism. They also serve as representative samples of Rosenbaum's unique brand of film writing. Among the highlights are memoirs of director Jacques Tati and maverick critic Manny Farber, celebrations of classics such as Gentlemen Prefer Blondes and The Manchurian Candidate, and considered reevaluations of Orson Welles and Woody Allen [Publisher description].
Theory and practice : the criticism of Jean-Luc Godard -- 'Film comment' journals, 1974-1977 : excerpts -- Edinburgh encounters : a consumers/producers guide-in-progress to four recent avant-garde films -- Barthes & film : 12 suggestions -- A bluffer's guide to Bèla Tarr -- They drive by night : the criticism of Manny Farber -- Ozu's 'Good morning' -- Aspects of 'Anatahan' -- Gold diggers of 1953 : Howard Hawk's 'Gentlemen prefer blondes' -- 'Gertrud' as nonnarrative : the desire for the image -- 'The Manchurian candidate' -- 'Othello' goes Hollywood -- Work and play in the house of fiction : on Jacques Rivette -- The tyranny of sensitivity -- Love films : a Cassavetes retrospective -- The death of Hulot -- Orson Welles's essay films and documentary fictions : a two-part speculation -- The importance of being perverse : Godard's 'King Lear' -- Alain Resnais and 'Mélo' -- Jerry Lewis's 'Hardly working' -- 'Doomed love' : the masterpiece you missed -- 'Raiders of the lost ark' -- Mapping the territory of Râúl Ruiz -- Notes toward the devaluation of Woody Allen -- Crass consciousness : 'Barton fink' -- Bird watching -- Jean Vigo's secret : L'atalante -- Guilty by omission -- His master's vice : Fuller's 'White dog' -- Government lies : 'The Panama deception' and 'Deep cover' -- A cinema of uncertainty : films by Michelangelo Antonioni.
Includes bibliographical references (pages 315-321) and index.
Print version record.
English.
JSTOR
Keywords: Motion pictures -- Reviews; Film criticism; Motion Pictures as Topic; Cinéma -- Comptes rendus; Critique cinématographique.; PERFORMING ARTS -- Film & Video -- History & Criticism; PERFORMING ARTS -- Film & Video; PERFORMING ARTS / Film / General; Film criticism; Motion pictures; Review; reviews (documents); Reviews; Reviews; Comptes rendus